Decision making & educational leadership: Comprehensive systematic review - Noor Ashikin Mat Shoib; Roslee Talip; Nursuhaidah Sukor (Global Academic Excellence, 2025)
This Systematic Literature Review (SLR) examines contemporary research on decision-making and educational leadership, focusing on studies from 2022 to 2024. The study addresses the increasing complexity of educational leadership by investigating key themes that impact leadership effectiveness in dynamic environments. A comprehensive search was conducted across Scopus, Web of Science (WoS), and ERIC databases, yielding a final dataset of 32 primary studies analyzed under the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework. The findings are organized into three major themes: (1) Leadership Skills and Professional Development, highlighting the competencies and training needed for effective decision-making; (2) Crisis Leadership and Adaptation, emphasizing the adaptability, communication skills, and resilience required to lead during challenging times; and (3) Inclusive and Data-Driven Decision-Making, which highlights the role of technology and collaborative approaches in fostering inclusivity and optimizing resource use. Quantitative analysis indicates that approximately 55% of the studies reported a significant link between data-driven decision-making and improved institutional outcomes, while 48% emphasized emotional intelligence as essential for managing crises. The review concludes that a multifaceted approach integrating professional skills, crisis adaptability, and inclusive, data-informed strategies is crucial for effective educational leadership. These insights provide valuable implications for policymakers and practitioners aiming to enhance leadership frameworks, suggesting that modern educational leaders must balance analytical and emotional competencies to meet diverse institutional demands effectively.